Take two, Birdie Maxwell [large type] - Scotch, Allison Winn (Thorndike Press large print top shelf., 2024)
"Birdie Robinson thought she'd gotten everything she wanted out of life: fame, adoration and an A-list career as Hollywood's most beloved ingenue. But after an on-set feud goes viral, she's forced to go into hiding in the one place where no one would think to find her: her childhood home. Wallowing in her bedroom, she stumbles upon an anonymous love letter from a former boyfriend and decides that a very public reunion with her nameless suitor could turn the wave of public opinion back in her favor. Life imitating art. What could go wrong? Elliot O'Brien, star reporter, believes firmly in facts, and he knows that life isn't an actual rom-com. Case in point, he's spent two decades repressing his long-simmering feelings for his twin sister's best friend, Birdie. But with his journalistic career cratering, and with Birdie back in town clutching an anonymous love letter, he realizes that chronicling her search for her long ago ex may be his opportunity to right some wrongs. As they hit the road in an ancient RV, Birdie and Elliot retrace her romantic history and come face to face with their own romantic missteps, all while grappling with whether or not happy endings are found only on the big screen--or whether their own happier ever after could be closer than they both ever imagined."--